Kajian Hukum Pembentukan UU Cipta Kerja Dalam Perspektif UU No.25 Tahun 2019 - Muhammad Dahlan Harahap (Jurnal Smart Hukum (JSH), 2022)
The process of establishing the Job Creation Law has established a series of principles, both formally and materially. The formation of the Job Creation Law tends to ignore the principles of the formation of laws and regulations, both formal and material principles. The formulation of the problem is how the design and ratification of Law No.11/2020 is in accordance with Law No.15/2019 concerning the Formation of Legislations, what is the position of Law No.11/2020 in the perspective of Law No.15/2019, and what is the impact of its implementation. Law No.11/2020 on the system of laws and regulations in force in Indonesia The research method used is descriptive analysis that leads to normative juridical legal research, namely research conducted by referring to legal norms, namely researching library materials or secondary materials . Secondary data by processing data from primary legal materials, secondary legal materials and tertiary legal materials. The results of the study indicate that the design and ratification of Law No. 11/2020 on Job Creation is not in accordance with Law no. 12/2011 Jo. Law No. 15/2019. With the Constitutional Court Decision No. 91/PUU-XVIII/2020, the Job Creation Law is considered conditionally unconstitutional. The impact of the implementation of Law No.11/2020 on the system of laws and regulations in force in Indonesia is that the Job Creation Law has procedural defects because in the process the public does not know the standard and official text relating to the Job Creation Act.